2021
DOI: 10.1111/1759-7714.14070
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of paraneoplastic neurological syndrome related to different pathological lung cancers

Abstract: Background Paraneoplastic syndrome is a distant effect caused by malignant tumors, which is related to the production of cellular immune response. The nervous system is the most common involved system of paraneoplastic syndrome. It is easy to be misdiagnosed. Lung cancer is the most common cancer relating to paraneoplastic neurological syndrome (PNS). Method This study retrospectively analyzed clinical data of patients with the combination of PNS and lung cancer between January 2005 and March 2021 at Qilu Hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
5
1
Order By: Relevance
“…These findings indicate that screening for SOX2, Hu, and P/Q‐type VGCC autoantibodies could capture the majority of SCLCs in patients with a related PNS, but this is insufficient to be a useful tumor marker in the absence of PNS. In contrast, another study did not find SOX2 antibodies in SCLC patients with PNS 40 . We found that 20% had P/Q‐tye VGCC or Hu autoantibodies, but did not include an SOX2 autoantibody assay in our study.…”
Section: Discussioncontrasting
confidence: 73%
“…These findings indicate that screening for SOX2, Hu, and P/Q‐type VGCC autoantibodies could capture the majority of SCLCs in patients with a related PNS, but this is insufficient to be a useful tumor marker in the absence of PNS. In contrast, another study did not find SOX2 antibodies in SCLC patients with PNS 40 . We found that 20% had P/Q‐tye VGCC or Hu autoantibodies, but did not include an SOX2 autoantibody assay in our study.…”
Section: Discussioncontrasting
confidence: 73%
“…Although PNS s occur in less than 0.01% of cancer patients, they are clinically important because neurological manifestations are usually diagnosed well before the underlying tumor. Lung adenocarcinoma belongs to the tumor types that were reported to give rise to PNS -inducing autoantibodies (42, 43). About 30 PNS -inducing onconeural antigens have been identified to date (44).…”
Section: Resultsmentioning
confidence: 99%
“…They are reported to occur in 0.3% of all malignancies, making them relatively rare conditions [ 2 ]. The majority of malignancies associated with PNS are lung cancers, with SCLC being the most common, whereas NSCLCs such as lung adenocarcinoma are rare [ 3 , 5 ]. In this case, given the background of NSCLC, the coexistence of neuroendocrine tumors was considered and assessed; however, both morphologically and immunohistochemically, this hypothesis was dismissed.…”
Section: Discussionmentioning
confidence: 99%